1995
DOI: 10.1159/000217153
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cerebral Perfusion following Reduction of Fibrinogen and Lipid Fractions

Abstract: High levels of plasma fibrinogen in cerebrovascular disease cause deterioration in the hemorheologic pattern, microcirculation and cerebral perfusion. We compared the value of hepa-rin-induced extracorporeal LDL precipitation (HELP) which is a method that safely and effectively reduces plasma fibrinogen and lipoproteins and so improves the hemorheologic pattern and blood flow properties. Regional cerebral blood flow (rCBF) was measured by the 133Xe SPECT clearance method. After first measuring rCBF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
2
10
0
1
Order By: Relevance
“…Clinical reports have demonstrated that HELP and DELP systems can effectively remove TC, TG, LDL, LP(a), and fibrinogen from plasma; reduce blood viscosity; and increase local regional blood flow (6,14) to produce an increase in regional cerebral blood flow by 19.9% (16). In the present animal study, DELP apheresis significantly reduced TC and FIG.…”
Section: Discussionsupporting
confidence: 55%
“…Clinical reports have demonstrated that HELP and DELP systems can effectively remove TC, TG, LDL, LP(a), and fibrinogen from plasma; reduce blood viscosity; and increase local regional blood flow (6,14) to produce an increase in regional cerebral blood flow by 19.9% (16). In the present animal study, DELP apheresis significantly reduced TC and FIG.…”
Section: Discussionsupporting
confidence: 55%
“…It could be shown that arteriosclerosis of the carotid artery is associated with an increased fibrinogen plasma level [18]. A decreased red cell transit time results in a decrease in microcirculation [19]. The HELP system (Braun Melsungen) is designated for extracorporeal elimination of fibrinogen, total cholesterol, LDL cholesterol and triglycerides.…”
Section: Ooooooooooooooooomentioning
confidence: 99%
“…In this connection, wholeblood plasma viscosity will be lowered and red cell transit time will be increased. The HELP application is followed by an increase in CBF, thus improving microcirculation [19]. In comparison to HELP application, the effect of PTX administration is rather modest.…”
Section: Ooooooooooooooooomentioning
confidence: 99%
“…The HELP system can effectively improve the parameters of hemorheology and the oxygentransfer properties of red blood cells in order to increase the cerebral blood flow. The study of Walzl et al showed that one HELP treatment can lead to the maximum increase in the regional cerebral blood flow by 19.9% (11).…”
Section: Discussionmentioning
confidence: 99%
“…The study of Walzl et al. showed that one HELP treatment can lead to the maximum increase in the regional cerebral blood flow by 19.9% (11).…”
Section: Discussionmentioning
confidence: 99%